Fragmentos da memória: contribuições à história da cidade de Caxias do Maranhão - Santos, Mariangela Santana Guimarães (Universidade do Vale do Rio dos Sinos, 2018)
Caxias, in the state of Maranhão, is a city with a vast repertoire in relation to cultural and historic patrimonial elements, either material or intangible ones: its architecture, economy, religiosity, the political, educational and social life wich are expressed in neighborhoods, big houses, factories, churches, schools and universities, squares, monuments, festivities, foods, poetry in short, a whole diversity of places, things and knowledges that can provide precious informations about the city’s formation process. From this assumption, the question arose as to how the historical discourses built on the city of Caxias can be perceived, through the bias of material and immaterial culture, as relevant, characterizing it as a place of memories, not only in the sense of elevation but especially as an object of reflection and questioning. Presenting, from oral testimonies, the fragments of the memories that will tell the story to the people who still pass through these spaces, is of the utmost importance. They are memories that marked the life of each inhabitant, each family, the habits and customs that generated a corpus of memory and that deserves to be understood, since it substantiates the composition of identities, especially of the younger ones, who need to know them to position themselves critically on the history and, in understanding it, acquire the foundations to value and give continuity to this process. Looking for this, we constructed the thesis from the accounts of five residents of different neighborhoods of the city, juxtaposing them to the end with formal academic thinking, based on the testimonies of three teachers, from different contexts related to the scope of production, custody and disclosure memory and history. The analysis of the material obtained from the research resulted in a complex relation of aspects of the life history of the deponents with the theme of the history and patrimony of the city. In this sense, we observe that through the memory of the deponents it was possible to unveil the details of a certain period, which allows them to express themselves in the condition of the main actors of the history of the neighborhood and city that reside, still maintaining a close relationship with it.
Keywords: Memória; História; Patrimônio; Cidade; Caxias; Maranhão; Memory; History; Patrimony; City; Caxias; Maranhão; ACCNPQ::Ciências Humanas::História